THE GENOCIDE IN CLOSING SPANISH ISLAM (THE STUDY OF ANDALUS FROM THE FALL OF GRANADA UP TO MORISCOS EXPULSION) - Ahmad Rifqi Maulana Zamzami (IAIN Syekh Nurjati Cirebon, 2016)
.This thesis focuses on Muslim circumstance under Christian hegemony from the fall of Islamic Andalusia up until Muslim ‘Moriscos’ expulsion in the seventeenth century, in which according to international law this example of annihilating group injuriously can effectively be classified as a genocide action. This study is based on the library research and the method used in this study is the historical research method with the qualitative descriptive approach as follows; Heuristic, source criticism, data interpretation, and historiography. In this research, the writer discusses some important points such as; a series of related event before Muslims lose their last besiege in Granada and some mistreatments conducted by the Spanish monarch toward Muslims after the fall of the last Islamic kingdom in Granada to which many scholars categorized it as a genocide action. Key words: Moriscos, Expulsion, Genocide.